(untitled) (Asian Journal of Agriculture, 2025)
Abstract. Barla A, Patel S, Swain SS, Parida S. 2025. Exploring the impact of vermicomposting on growth of wheat under organic farming system. Asian J Agric 9: 298-304. Climate Resilient Agriculture (CRA) includes the sustainable use of natural resources through crop production to attain long-term higher productivity and income from farms under variable climatic conditions. Though organic farming is criticized as a lower-yielding system than the conventional system and is unable to meet the food demand of the world’s population, still simultaneously it has a positive impact on the environment and on maintaining the soil ecosystem including a positive impact on human health. Therefore, consumer demand for organic products is increasing which encourages organic farming systems. This paper focuses on integrating organic farming particularly the use of organic compost in promoting soil health and wheat crop growth. In this study, vermicompost and cow dung compost were applied to observe its impact on the growth of wheat (Triticum aestivum L.) crops under pot experiments. A pot containing normal soil was taken as control, soil: cow dung (2:1) and vermicompost was applied in different proportions of soil and vermicompost (S: V) in 1:1, 2:1, and 4:1 ratios to evaluate the vegetative crop growth. For wheat crop, the application of vermicompost (S: V with 2:1) in soil showed better results on crop growth than the cow dung compost (S: C with 2:1). Mineral contents of leaf were also analyzed by X-ray fluorescence (XRF) study and detected more in the leaves of wheat plant raised in S: V with (2:1) than the S: C (2:1) pots. Organic farming systems can be used for superior nutritional qualities in comparison to conventional systems.